If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + 4 + -3i)(x + -4 + 3i) = 0 Reorder the terms: (5 + x)(x + 4 + -3i)(x + -4 + 3i) = 0 Reorder the terms: (5 + x)(4 + -3i + x)(x + -4 + 3i) = 0 Reorder the terms: (5 + x)(4 + -3i + x)(-4 + 3i + x) = 0 Multiply (5 + x) * (4 + -3i + x) (5(4 + -3i + x) + x(4 + -3i + x))(-4 + 3i + x) = 0 ((4 * 5 + -3i * 5 + x * 5) + x(4 + -3i + x))(-4 + 3i + x) = 0 ((20 + -15i + 5x) + x(4 + -3i + x))(-4 + 3i + x) = 0 (20 + -15i + 5x + (4 * x + -3i * x + x * x))(-4 + 3i + x) = 0 Reorder the terms: (20 + -15i + 5x + (-3ix + 4x + x2))(-4 + 3i + x) = 0 (20 + -15i + 5x + (-3ix + 4x + x2))(-4 + 3i + x) = 0 Reorder the terms: (20 + -15i + -3ix + 5x + 4x + x2)(-4 + 3i + x) = 0 Combine like terms: 5x + 4x = 9x (20 + -15i + -3ix + 9x + x2)(-4 + 3i + x) = 0 Multiply (20 + -15i + -3ix + 9x + x2) * (-4 + 3i + x) (20(-4 + 3i + x) + -15i * (-4 + 3i + x) + -3ix * (-4 + 3i + x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 ((-4 * 20 + 3i * 20 + x * 20) + -15i * (-4 + 3i + x) + -3ix * (-4 + 3i + x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 ((-80 + 60i + 20x) + -15i * (-4 + 3i + x) + -3ix * (-4 + 3i + x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + (-4 * -15i + 3i * -15i + x * -15i) + -3ix * (-4 + 3i + x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 Reorder the terms: (-80 + 60i + 20x + (60i + -15ix + -45i2) + -3ix * (-4 + 3i + x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + (60i + -15ix + -45i2) + -3ix * (-4 + 3i + x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + 60i + -15ix + -45i2 + (-4 * -3ix + 3i * -3ix + x * -3ix) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 Reorder the terms: (-80 + 60i + 20x + 60i + -15ix + -45i2 + (12ix + -3ix2 + -9i2x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + 60i + -15ix + -45i2 + (12ix + -3ix2 + -9i2x) + 9x * (-4 + 3i + x) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + 60i + -15ix + -45i2 + 12ix + -3ix2 + -9i2x + (-4 * 9x + 3i * 9x + x * 9x) + x2(-4 + 3i + x)) = 0 Reorder the terms: (-80 + 60i + 20x + 60i + -15ix + -45i2 + 12ix + -3ix2 + -9i2x + (27ix + -36x + 9x2) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + 60i + -15ix + -45i2 + 12ix + -3ix2 + -9i2x + (27ix + -36x + 9x2) + x2(-4 + 3i + x)) = 0 (-80 + 60i + 20x + 60i + -15ix + -45i2 + 12ix + -3ix2 + -9i2x + 27ix + -36x + 9x2 + (-4 * x2 + 3i * x2 + x * x2)) = 0 Reorder the terms: (-80 + 60i + 20x + 60i + -15ix + -45i2 + 12ix + -3ix2 + -9i2x + 27ix + -36x + 9x2 + (3ix2 + -4x2 + x3)) = 0 (-80 + 60i + 20x + 60i + -15ix + -45i2 + 12ix + -3ix2 + -9i2x + 27ix + -36x + 9x2 + (3ix2 + -4x2 + x3)) = 0 Reorder the terms: (-80 + 60i + 60i + -15ix + 12ix + 27ix + -3ix2 + 3ix2 + -45i2 + -9i2x + 20x + -36x + 9x2 + -4x2 + x3) = 0 Combine like terms: 60i + 60i = 120i (-80 + 120i + -15ix + 12ix + 27ix + -3ix2 + 3ix2 + -45i2 + -9i2x + 20x + -36x + 9x2 + -4x2 + x3) = 0 Combine like terms: -15ix + 12ix = -3ix (-80 + 120i + -3ix + 27ix + -3ix2 + 3ix2 + -45i2 + -9i2x + 20x + -36x + 9x2 + -4x2 + x3) = 0 Combine like terms: -3ix + 27ix = 24ix (-80 + 120i + 24ix + -3ix2 + 3ix2 + -45i2 + -9i2x + 20x + -36x + 9x2 + -4x2 + x3) = 0 Combine like terms: -3ix2 + 3ix2 = 0 (-80 + 120i + 24ix + 0 + -45i2 + -9i2x + 20x + -36x + 9x2 + -4x2 + x3) = 0 (-80 + 120i + 24ix + -45i2 + -9i2x + 20x + -36x + 9x2 + -4x2 + x3) = 0 Combine like terms: 20x + -36x = -16x (-80 + 120i + 24ix + -45i2 + -9i2x + -16x + 9x2 + -4x2 + x3) = 0 Combine like terms: 9x2 + -4x2 = 5x2 (-80 + 120i + 24ix + -45i2 + -9i2x + -16x + 5x2 + x3) = 0 Solving -80 + 120i + 24ix + -45i2 + -9i2x + -16x + 5x2 + x3 = 0 Solving for variable 'i'. The solution to this equation could not be determined.
| Y/-15-122=-88 | | 420=10x(10) | | 2c+7=7c+52 | | 3-8y=-1 | | x-7y+y-3-2x+6z= | | (3x-3y)2+18xy= | | 1.15=(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x) | | 4x/3+=2 | | -2x+6=-7x+14 | | 4(3x-2)-5(2-x)= | | 17.01y=6.3 | | 9a-6(a+5)= | | .2*n=48 | | (X/4)+3=5 | | 5p-2=9p-2 | | 14c-6=7c-6 | | 10f+4=3f-59 | | 12x-(x*x)=36 | | 3(2a-3b)-4b(4a-4)= | | Z^2+6z-20=00 | | -6w-45=-9(w+8) | | 9x-5y=12 | | Z^2+6x-16=0 | | 50x^2+15x-2=(5x+2) | | 4p-1=9+17 | | 6x-10=6+10 | | 9q+1=4q-44 | | 2=3c+11 | | 4x+40=12x-102 | | (3/2)+4=5 | | x(8+9)= | | 3x/4-3.2=5.3-2x/3 |